Postprandial Regulation of Hepatic MicroRNAs Predicted to Target the Insulin Pathway in Rainbow Trout - Mennigen, Jan A.; Panserat, Stéphane; Larquier, Mélanie; Plagnes-Juan, Elisabeth; Medale, Françoise; Seiliez, Iban; Skiba-Cassy, Sandrine (PLOS ONE, 2012)
Rainbow trout are carnivorous fish and poor metabolizers of carbohydrates, which established this species as a model organism to study the comparative physiology of insulin. Following the recent characterisation of key roles of several miRNAs in the insulin action on hepatic intermediary metabolism in mammalian models, we investigated the hypothesis that hepatic miRNA expression is postprandially regulated in the rainbow trout and temporally coordinated in the context of insulin-mediated regulation of metabolic gene expression in the liver. To address this hypothesis, we used a time-course experiment in which rainbow trout were fed a commercial diet after short-term fasting. We investigated hepatic miRNA expression, activation of the insulin pathway, and insulin regulated metabolic target genes at several time points. Several miRNAs which negatively regulate hepatic insulin signaling in mammalian model organisms were transiently increased 4 h after the meal, consistent with a potential role in acute postprandial negative feed-back regulation of the insulin pathway and attenuation of gluconeogenic gene expression. We equally observed a transient increase in omy- miRNA-33 and omy-miRNA-122b 4 h after feeding, whose homologues have potent lipogenic roles in the liver of mammalian model systems. A concurrent increase in the activity of the hepatic insulin signaling pathway and the expression of lipogenic genes (srebp1c, fas, acly) was equally observed, while lipolytic gene expression (cpt1a and cpt1b) decreased significantly 4 h after the meal. This suggests lipogenic roles of omy-miRNA-33 and omy-miRNA-122b may be conserved between rainbow trout and mammals and that these miRNAs may furthermore contribute to acute postprandial regulation of de novo hepatic lipid synthesis in rainbow trout. These findings provide a framework for future research of miRNA regulation of hepatic metabolism in trout and will help to further elucidate the metabolic phenotype of rainbow trout.